ANALYSIS OF ACCESSIBILITY OF PEOPLE WITH SENSORY DISABILITIES IN RSUD PASAR MINGGU - Suryoputra, Daffaldo; Basabih, Masyitoh; Mulyani, Fify (UI Scholars Hub, 2024)
People with a disability is someone who has conditions, whether physically and mentally that make a person experience difficulty in certain conditions and interact with their environment. Pasar Minggu Regional Hospital (RSUD Pasar Minggu) has achieved a general patient satisfaction indicator with satisfaction rate of 90% in 2022. This satisfaction indicator mainly comes from infrastructure and facility factors, along with the competence of service providers and costs. As a regional referral hospital, this hospital certainly has patients with physical limitations due to disabilities or illnesses. To ensure patient satisfaction can also be felt by patients with physical limitations, this study aimed to get an overview regarding the accessibility of health service facilities for persons with sensory disabilities at RSUD Pasar Minggu, both physically and non-physically. This qualitative study was supported by several data collection including observation, document review, and in-depth interviews with patients with sensory disabilities, as well as health workers at in the Eye polyclinic and ENT polyclinic in 2023. The results showed that physical accessibility at RSUD Pasar Minggu already includes information boards, guiding blocks, handrails, special information counters, while braille and TV text are in the process of planning to be provided at the hospital. Meanwhile, non-physical accessibility includes training for healthcare providers, socialization of health services, as well as special communication for people with disabilities which have been carried out quite well and have provided satisfaction for patients with visual and hearing impairments in terms of the quality of health services at RSUD Pasar Minggu.